Factors affecting consumer purchasing decisions in Malaysia automotive industry - Chan, Chor Yarn (2016)
The Malaysian automobile market has been booming drastically for the past decades. The number of vehicles registered for the year 2005 was 16,440 units and this has increased to 40,753 units in the year 2013 (Road Transport Department Malaysia, 2015). Various automotive manufacturers have entered the market since the Proton monopoly was lifted have opened up numerous vehicle segments that now provide a wide-range of options to the consumers. And this phenomenon has increased keen competitions among each vehicle segment, thus creating a highly competitive automotive market. The purpose of this project paper is to identify factors that influence the consumer car-purchase decisions in Malaysia. The focus of this study is to determine and analyse the influence of economic, psychological, socio-cultural and demographic factors that affect the purchasing decisions of Malaysian automotive users. The research question seeks answers to how consumer purchasing decisions, based on different influencing factors, affect the automotive market in Malaysia. The research method is based on descriptive research design. The target population is 200 adults within the working age bracket (18 to 60 years) who are legally entitled to purchase a car in Malaysia, with a valid driver's license. Simple random sampling technique was used to procure responses from a questionnaire survey. Through various online forums, data collected were processed and recoded into inputs format recognised by the Statistical Package for Social Sciences (SPSS), and analysed using descriptive and inferential statistics of the SPSS program. The results were presented in tables and figures. The study concludes that consumer car-purchasing decisions were not influenced by a solitary factor but a combination of multiple attributes from the four factors, namely, economic, psychological, socio-cultural and demographic factors. A recommended action of this study, in such a complex context, suggest that future researchers develop products with specific features according to user preferences, and marketers formulate explicit marketing strategies to capture potential target consumers.